Mild Cognitive Impairment Staging Yields Genetic Susceptibility, Biomarker, and Neuroimaging Differences - Moore, Elizabeth E.; Liu, Dandan; Pechman, Kimberly R.; Acosta, Lealani Mae Y.; Bell, Susan P.; Davis, L. Taylor; Blennow, Kaj; Zetterberg, Henrik; Landman, Bennett A.; Schrag, Matthew S.; Hohman, Timothy J.; Gifford, Katherine A.; et al. (Frontiers in Aging Neuroscience, 2020)
Introduction: While Alzheimer’s disease (AD) is divided into severity stages, mild cognitive impairment (MCI) remains a solitary construct despite clinical and prognostic heterogeneity. This study aimed to characterize differences in genetic, cerebrospinal fluid (CSF), neuroimaging, and neuropsychological markers across clinician-derived MCI stages. Methods: Vanderbilt Memory & Aging Project participants with MCI were categorized into 3 severity subtypes at screening based on neuropsychological assessment, functional assessment, and Clinical Dementia Rating interview, including mild (n=18, 75±8 years), moderate (n=89 72±7 years), and severe subtypes (n=18, 78±8 years). At enrollment, participants underwent neuropsychological testing, 3T brain magnetic resonance imaging (MRI), and optional fasting lumbar puncture to obtain CSF. Neuropsychological testing and MRI were repeated at 18-months, 3-years, and 5-years with a mean follow-up time of 3.3 years. Ordinary least square regressions examined cross-sectional associations between MCI severity and apolipoprotein E (APOE)-4 status, CSF biomarkers of amyloid beta (A), phosphorylated tau, total tau, and synaptic dysfunction (neurogranin), baseline neuroimaging biomarkers, and baseline neuropsychological performance. Longitudinal associations between baseline MCI severity and neuroimaging and neuropsychological trajectory were assessed using linear mixed effects models with random intercepts and slopes and a follow-up time interaction. Analyses adjusted for baseline age, sex, race/ethnicity, education, and intracranial volume for MRI models. Results: Stages differed at baseline on APOE-4 status (early<middle=late; p-values<0.03) and CSF A (early>middle=late), phosphorylated and total tau (early=middle<late; p-values<0.05), and neurogranin concentrations (early=middle<late; p-values<0.05). MCI stage related to greater longitudinal cognitive decline, hippocampal atrophy, and inferior lateral ventricle dilation (early<late; p-values<0.03). Discussion: Clinician staging of MCI severity yielded longitudinal cognitive trajectory and structural neuroimaging differences in regions susceptible to AD neuropathology and neurodegeneration. As expected, participants with more severe MCI symptoms at study entry had greater cognitive decline and grey matter atrophy over time. Differences are likely attributable to baseline differences in amyloidosis, tau, and synaptic dysfunction. MCI staging may provide insight into underlying pathology, prognosis, and therapeutic targets.